Assessing the Prevalence, Predictors, and Consequences of Secondary Traumatic Stress Among Emergency Nurses in Palestine During the COVID-19 Pandemic - Basma Salameh PhD, RN; Abdalla Ghassen Daibes MSN, RN; Jamal Qaddumi PhD, RN (SAGE Publishing, 2023)
Introduction Emergency nurses who are working in direct contact with COVID-19 patients are at an increased risk of developing secondary traumatic stress disorder. This study aimed to assess the prevalence, predictors, and consequences of secondary traumatic stress among emergency nurses in Palestine during the COVID-19 pandemic Methods The study utilized a cross-sectional design and recruited a total of 189 emergency nurses from multiple healthcare centers in Palestine. Data collected from January 21, 2021, to March 31, 2021. Results The study revealed that emergency nurses had a high degree of secondary traumatic stress with the prevalence of high to severe symptoms of secondary traumatic stress being 61% of the total participants. In terms of predictors, the results showed that years of experience, level of education, burnout, and organizational support were significantly correlated with secondary traumatic stress and thus that years of experience and burnout are predictors of secondary traumatic stress. Conclusion Based on our findings, nurses in emergency departments in Palestine have a high degree of secondary traumatic stress disorder which impacts their lives on a personal and professional level.